1978
DOI: 10.1128/aac.13.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of a Beta-Lactamase from Vibrio parahaemolyticus by a New Automated Microiodometric Technique

Abstract: A number of characteristics were determined with a new automated method for a partially purified ,-lactamase from Vibrio parahaemolyticus. The enzyme had a molecular weight of 28,000 by gel filtration, a pH optimum between 6.5 and 7.0, and a temperature optimum at 36°C. With penicillin G as the substrate, the Km value for the ,B-lactamase was 54.4 IAM. The ,B-lactamase was inhibited by cloxacillin but not by p-chloromercuribenzoate. The enzyme was similar but not identical to /8-lactamases from gram-negative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Laboratories having a spectropho- fast analyzer can achieve great accuracy by rapid replicate analysis similar to that reported here and earlier by DeBell et al (4). The latter investigators adapted the microiodometric method to a Rotochem and reported excellent enzyme kinetic results for a Vibrio parahaemolyticus beta-lactamase (4). PADAC can also be used as the beta-lactamlabile substrate for inhibition studies (6a, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratories having a spectropho- fast analyzer can achieve great accuracy by rapid replicate analysis similar to that reported here and earlier by DeBell et al (4). The latter investigators adapted the microiodometric method to a Rotochem and reported excellent enzyme kinetic results for a Vibrio parahaemolyticus beta-lactamase (4). PADAC can also be used as the beta-lactamlabile substrate for inhibition studies (6a, 7).…”
Section: Discussionmentioning
confidence: 99%
“…AGENTS CHEMOTHER. (4), Citrobacter (unidentified species [10]), Enterobacter gergoviae (2), E. sakazakii (5), Klebsiella ozaenae (6), K. rhinoscleromatis (3), Providencia alcalifaciens (2), Serratia liquefaciens (5), S. rubidaea (2), and Yersinia enterocolitica (4). (12), P. fluorescens-putida (8), P. putrefaciens (1), P. stutzeri (18), P. acidovorans (3), P. alcaligenes (6), P. paucimobilis (1), P. testosteroni (5) and Pseudomonas sp.…”
mentioning
confidence: 99%
“…Only one strain, V. alginolyticus 7608, possessed unusually high SOD levels. Although we have no direct explanation for this phenomenon, we have noted that this strain synthesizes higher amounts of other enzymes, such as ,8-lactamases, than the other vibrios (9).…”
Section: Resultsmentioning
confidence: 72%